Of Levinas and Shakespeare: "to see another thus" - Lehnhof, Kent Russell; Gold, Moshe; Goodhart, Sandor ca. 20./21. Jh. (Purdue University Press, 2018)
10: Culinary Skepticism in As You Like It and Montaigne's "Of Experience"11: Staging Humanity in As You Like It and Pirkei Avot; Works Cited; Notes on Contributors; Index